Assessment of the Effect of Flooding on Agricultural Lands in Kaharo Sub-County of Kabale District South Western Uganda. - Nyakiti, Dorcas Awino (Kabale University, 2023)
In the last three decades, the impacts of flooding have increasingly assumed from significant to threatening proportions in Kaharo sub-county villages like Kitare, Nyakigugwe, Nkumbura, Kizinga, Karehe resulting in loss of lives and destroying farm lands. The purpose of this study was therefore assessment of the effects of flooding on agricultural lands in Kaharo sub county of Kabale district south western Uganda. The study was guided by the specific objectives which include investigating the causes of flooding on agricultural lands in Kaharo sub county, establishing the effects of flooding on agricultural lands in Kaharo sub county, and assessing the possible solutions to the effects of flooding on agricultural lands in Kaharo sub county of Kabale district south western Uganda. The study employed descriptive survey design utilizing both qualitative and quantitative data collection and analyses methods. Using simple random and purposive sampling techniques, a total of 84 respondents were selected to participate in the study. Focused group discussion and interviewing methods of data collection were used in this study. Rapid urbanization, population growth and high Rainfall Intensities were the causes of flooding on agricultural lands in Kaharo sub county Kabale district reported by 49%, 56% and 32%), respectively (Table 4.1). Other causes of flooding were location of settlement on flood plain (48%), lack of awareness and information (2%), poverty (7%), unprotected flood areas, standing crops and livestock (30%) and lastly transition in cultural practices (24%). Loss of life (52) was the major effect of flooding on agricultural lands in Kaharo sub county Kabale district (Table 4.2), 49% of the respondents recorded that damage to crops and food supplies were the effects of flooding in an area whereas 46% of the respondents mentioned that Famine was also an effect of flooding due to destruction of crops and other agricultural lands. It was also concluded that 60% of the respondents suggested that there should be wetland restoration in the area, the need for community based natural resource management which helps in the conservation of wetlands (44%), 38% of the respondents suggested that early warning systems should be put in place to find out different mitigation measures for conservation of agricultural lands whereas 30% of the respondents suggested that there was need for massive education (Table 4.3). The study also recommended areas for further studies like assessment of the effects of flooding on agricultural production in Kaharo sub-county and assessing Vulnerability of Peri-Urban Areas to Floods.